AI POWERED SMART HEADLIGHT SYSTEM USING IOT AND DEEP LEARNING - Ananth S; Mekala R; Shrihari S; Bhadrinathan S B; Vignesh R; Saravanan S (Utilitas Mathematica, 2025)
This project showcases a smart headlight system that is powered by artificial intelligence (AI). It uses deep learning and the Internet of Things (IoT) to make nighttime driving safer and less glarey. In order to detect approaching cars in real-time, the suggested system incorporates a front-facing camera with sophisticated object detection algorithms. To keep the user's vision unobstructed and other drivers' eyes protected from glare, a microprocessor uses the detected position to dynamically alter the brightness of individual headlight LEDs. Without sacrificing visibility, this selective dimming mechanism guarantees comfort and safety. Internet of Things (IoT) technology allows for remote system updates and monitoring, which improves performance over time and makes it more adaptable to different driving situations. Furthermore, by regulating just the essential LED segments, the system encourages energy efficiency. In sum, the intelligent headlight solution improves upon traditional systems in important ways, making driving both safer and more efficient.